Effect of Ti content on the metallization layer and copper / alumina brazed joint. Issue 16 (November 2017) - Fu, W.; Hu, S.P.; Song, X.G.; Jin, C.; Li, J.X.; Zhao, Y.X.; Cao, J.; Wang, G.D.
Abstract: The effects of Ti content on the evolution of metallization layer and microstructure and shear strength of copper / alumina brazed joint were investigated. A good bonded metallization layer in β-Sn matrix containing Ti6 Sn5 phases was obtained on the surface of alumina at 900 °C for 30 min. Active Ti dissolved into liquid SAC and reacted with alumina to form TiO layer resulting in the spreading of melt. Therefore a more flat metallization layer covered on alumina as more Ti added into SAC. On the other hand, due to the violent reaction between element Ti and Sn, Ti6 Sn5 precipitated in melt leading to the reduction of the fluidity of melt, and a discontinuous metallization layer was obtained for SAC-8%Ti. After metallization process, alumina was brazed to copper at 600 °C for 5 min. Typical microstructure of brazed joint was copper / Cu3 Sn layer / Cu6 Sn5 layer / β-Sn layer containing Ti6 Sn5 phases and Al2 O3 particles / alumina. As the increase of Ti content, more Ti6 Sn5 phases existed in brazing seam, which enhanced the shear strength of brazed joint, at 6%Ti, the highest value of 25 MPa was achieved. With the further increase of Ti content, the effective bonding area of copper / alumina brazed joint decreased and a corresponding lower shear strength was obtained.